Assessment of priorities, quality, and inclusivity of digital therapeutics trials in China - Ziming Wang; Xinxin Xia; Weijia Lu; Yuguo Ye; Jin Xu (npj Digital Medicine)
Abstract Digital therapeutics (DTx) are software-driven solutions for prevention, treatment, and management of medical conditions. Despite a pro-DTx momentum in China, global DTx trial assessments overlooked the country. We identified 756 DTx trials in China and analyzed their characteristics and quality parameters. Over 70% were funded by governments, hospitals, and universities, with tertiary hospitals in eastern China leading most trials. 44.8% used automated DTx, with 39.2% DTx-guided. Most trials focused on management (52.5%) and treatment (38.1%), with few on prevention (9.4%). Mental, behavioral, or neurodevelopmental disorders represented the leading condition category of focus. Recent declines in median sample size, median duration, and mean number of sites were noted. Only 18% of trials were at low overall risk of bias. While recognizing the rapid development of DTx trials in China, we call for better trial design and methodological rigor, prioritization of preventive and primary care, wider condition category scope, and higher inclusivity.